2019
DOI: 10.3390/plants8120534
|View full text |Cite
|
Sign up to set email alerts
|

Methyljasmonate Elicitation Increases Terpenoid Indole Alkaloid Accumulation in Rhazya stricta Hairy Root Cultures

Abstract: Methyl jasmonate is capable of initiating or improving the biosynthesis of secondary metabolites in plants and therefore has opened up a concept for the biosynthesis of valuable constituents. In this study, the effect of different doses of methyl jasmonate (MeJA) elicitation on the accumulation of terpenoid indole alkaloids (TIAs) in the hairy root cultures of the medicinal plant, Rhazya stricta throughout a time course (one-seven days) was investigated. Gas chromatography-mass spectrometry (GC-MS) analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Since, for many reasons, the naturally occurring plant material in the environment is not able to satisfy the demand, a lot of attention is focused on obtaining high‐yield in vitro plant cultures that are an excellent source of valuable secondary metabolites. Multiple research results show that the efficient synthesis of anthraquinones, phenolics and flavonoids or terpenoid indole alkaloid is possible thanks to the use of many different strategies [32–35] . Secondary metabolites, demonstrating a diverse set of properties in the plant (influencing its development, protection against the adverse effects of external factors, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Since, for many reasons, the naturally occurring plant material in the environment is not able to satisfy the demand, a lot of attention is focused on obtaining high‐yield in vitro plant cultures that are an excellent source of valuable secondary metabolites. Multiple research results show that the efficient synthesis of anthraquinones, phenolics and flavonoids or terpenoid indole alkaloid is possible thanks to the use of many different strategies [32–35] . Secondary metabolites, demonstrating a diverse set of properties in the plant (influencing its development, protection against the adverse effects of external factors, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have confirmed that the phytohormone methyl jasmonate (MeJA) can enhance the biosynthesis of secondary metabolites in officinal plants [ 23 25 ]. MeJA, as an elicitor, plays an important role in the signal transduction of alkaloids biosynthesis and has been reported to promote the accumulation of metabolites in Dendrobium plants [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…So far, many examples have been reported in which the use of such an approach resulted in higher productivity [ 10 , 11 , 12 ]. Akhgari et al [ 13 ], studying the effects of different doses of methyl jasmonate (MeJA) on the accumulation of terpenoid indole alkaloids in the hairy roots of the Rhazya stricta, showed an increased content of alkaloids compared to non-elicited cultures. Additionally, Wei et al [ 14 ] showed that kaurene synthase-like gene overexpression combined with methyl jasmonate treatment enhanced tanshinone production from Salvia miltiorrhiza hairy roots.…”
Section: Introductionmentioning
confidence: 99%